Physicochemical Investigation and Analysis of Nypa Sap (Nypa fruticans Wurmb) using a Novel Collecting Device - Ana Sakura, Zainal Abidin; Hanif, Mohd Teddy; Mohd Razip, Asaruddin; Mohd Zulhatta, Kifli; Rasli, Muslimen; Marini, Sawawi; Abang Ahmad, Dzulfakhri; Kasyful Azhim, Yussof; Fredy, Muhamad Firdaus; Khairul Fikri, Tamrin (UNIMAS Publisher, 2024)
A sweetener from Nypa fruticans Wurmb offers significant health benefits. The traditional process of sap tapping requires careful attention to enhance cleanliness. In this research, a nypa sap harvesting device has been developed, and a time study for its installation has been conducted. The physicochemical properties of the sap gathered from the device were evaluated and compared with the traditional method in terms of total soluble solids(TSS) reading, pH level, total dissolved solid (TDS) and electrical conductivity (EC) value, and glucose content. Both methods showed no significant difference, with an average TSS reading of 14 to 15 °brix, pH of 3.57-3.97, glucose content of 25.9 to 32.4, TDS of 2340-2726 ppm, and EC reading of 4679-5472 μs/cm. Slight differences in physicochemical properties were observed due to the random selection of trees for the experiment. The use of the device was found to improve the physical cleanliness of the sap by 97% and chemical purity by 7% to 11%. The colour of the sap collected with the device was milky white compared to the traditional bamboo method, resulting in a yellowish-white sap. The time study showed a 40% improvement compared to the first trial, indicating the practicality of the device, which can be easily installed by the operator. The physicochemical properties of the sap collected using the device can be further improved with the addition of preservatives. The findings are expected to enhance sap harvesting hygiene and the quality of sap, directly affecting the quality and benefits of the derived products.